(untitled) (Research, Society and Development, 2022)
This study investigated the influence and perception of parents on the global development of children from birth to 3 years and 11 months of age, during the social distancing period in the COVID-19 pandemic in Brazil. An online survey was shared and answered anonymously by parents between December 2020 and February 2021. The survey consisted of multiple-choice questions considering: children and family characteristics, parents’ perception of their children’s development, parents’ abilities and limitations on children’s development and play, and choice of stimuli offered to their children. General descriptive analyses and binary logistic regression were performed. All parents (n=142) reported stimulating new global developmental skills during the pandemic. They (59.2%) reported spending more time playing with their children during the pandemic than before. Most of them let their children play freely (89%) and let them spend more time playing with screen devices (66.1%) during the pandemic. As children were older, parents were more likely to agree that they have been doing activities that could negatively influence their global development, and higher frequency of screen time (p<.005). We discuss the possible advantages and difficulties parents have encountered in stimulating their children’s global development during this period and their perception of these aspects. This may help guide professionals and shape public policies to strengthen facilities and confront difficulties during pandemic periods. This study might help to understand possible issues that young children and their parents may confront in the near future, as a consequence of the pandemic.